Canonical Bone Morphogenetic Protein Signaling Regulates Expression of Aquaporin-4 and Its Anchoring Complex in Mouse Astrocytes - Skauli, Nadia; Savchenko, Ekaterina; Ottersen, Ole Petter; Roybon, Laurent; Amiry-Moghaddam, Mahmood (Frontiers in Cellular Neuroscience, 2022)
Aquaporin-4 (AQP4) is the predominant water channel in the brain; it is enriched in astrocytic foot processes abutting vessels where it is anchored through an interaction with the dystrophin-associated protein (DAP) complex. Enhanced expression with concomitant mislocalization of AQP4 along astrocyte plasma membranes is a hallmark of several neurological conditions. Thus, there is an urgent need to identify which signaling pathways dictate AQP4 microdistribution. Here we show that canonical bone morphogenetic proteins (BMPs), particularly BMP2 and 4, upregulate AQP4 expression in astrocytes and dysregulate the associated DAP complex by differentially affecting its individual members. We further demonstrate the presence of BMP receptors and Smad1/5/9 pathway activation in BMP-treated astrocytes. Our analysis of the adult mouse brain reveals BMP2 and 4 in neurons and in a subclass of endothelial cells and activated Smad1/5/9 in astrocytes. We conclude that the canonical BMP-signaling pathway might be responsible for regulating the expression of AQP4 and of DAP complex proteins that govern the subcellular compartmentation of this aquaporin.